Poem-ando Além Fronteiras: dez poetas contemporâneas irlandesas e portuguesas. Poem-ing Beyond Borders: ten contemporary Irish and Portuguese women poets. Ed. & Trans. Gisele Giandoni Wolkoff. - Palácios, Manuela (ABEI Journal, 2011)
Poem-ando Além Fronteiras: dez poetas contemporâneas irlandesas e portuguesas. Poem-ing Beyond Borders: ten contemporary Irish and Portuguese women poets. Ed. & Trans. Gisele Giandoni Wolkoff. Coimbra: Terra Ocre-Palimage, 2011